2019
DOI: 10.1186/s13027-019-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of cytokine levels in triage and risk prediction for women with persistent high-risk human papilloma virus infection of the cervix

Abstract: Background Cervical cancer is a common cancer among women worldwide and is closely related to high-risk human papillomavirus infection (HR-HPV). The immune microenvironment is thought to play an essential role in viral infection and cancer development; however, this relationship remains controversial. Cytokines are an important part of the immune system. Therefore, in this study, we explored changes in cervical cytokine levels of women with persistent HR-HPV infection and determined the value of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
1
16
0
6
Order By: Relevance
“…In contrast, we found that IL-2 levels were significantly decreased in HSIL and LSIL samples compared to NSIL samples. This result agrees with a recent study showing that cervical disease severity was inversely related to IL-2 levels [13]. Although involved in Th2 differentiation, IL-2 is also considered an important Th1 pro-inflammatory cytokine [29,33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, we found that IL-2 levels were significantly decreased in HSIL and LSIL samples compared to NSIL samples. This result agrees with a recent study showing that cervical disease severity was inversely related to IL-2 levels [13]. Although involved in Th2 differentiation, IL-2 is also considered an important Th1 pro-inflammatory cytokine [29,33].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we compared the cytokine profiles of cervical biopsies with histopathological diagnoses, using a panel that included key cytokines of each type of immune response: Th1 (IL-12 and IFN-γ), Th2 (IL-2 and IL-4), Treg (IL-10), and Th17 (IL-23 and IL-17) [13][14][15][16][17]. IL-2 and IL-23 were downregulated in HPV lesions, but the levels of the other cytokines displayed no significant association with lesion diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can activate healing process and eliminate the injurious stimuli, which is considered as a mechanism of innate immunity [54]. Inflammation caused by genital infection can produce nonspecific protective antimicrobial oxidants which can also contribute to oxidative damage to host DNA, resulting in cancer [55].Inflammation related factors, like IL6, is an important factor promoting the progression of the disease and the development of tumors [56]. Many studies supported that inflammation is possibly a risk factor for carcinogenesis [15].Our study clearly showed a positive relationship between inflammation and HSIL, and 56.2% of HISL patients had CIN3.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos estudos que avaliou a imunidade no colo uterino em mulheres com lesões intraepiteliais cervicais induzidas pelo HPV realizou a quantificação de citocinas no muco cervical ou lavado cervicovaginal (CASTLE et al, 2002;MARKS et al, 2011;TELESHEVA et al, 2012;SCOTT et al, 2013;EKALAKSANANAN et al, 2014;IWATA et al, 2015;DANIILIDIS et al, 2016;LI et al, 2019;OTANI et al, 2019). No entanto, muitas citocinas são expressas a partir de células específicas que não estão localizadas na superfície do epitélio e a avaliação da secreção cervicovaginal estaria medindo apenas o transbordamento destas substâncias para o lúmen vaginal.…”
Section: Agcunclassified